2003
DOI: 10.1016/s1071-5576(03)00089-3
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling and uterine contractility

Abstract: Changes in Ca(2+) signals within the myometrium have important functional consequences, as they determine contractility. We show that the basic phasic nature of uterine contractions, which is essential for successful labor, is critically dependent on Ca(2+) influx through voltage-gated L-type Ca(2+) channels, and hence in turn, on membrane potential. Thus changes in ion channel expression around term will play an important role in governing uterine excitability and contractility. There remains uncertainty abou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
105
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(110 citation statements)
references
References 154 publications
1
105
0
4
Order By: Relevance
“…Oxytocin and PGF 2␣ cause myometrium contractions by acting on oxytocin and prostaglandin FP receptors, respectively (Zingg and Laporte, 2003;Myatt and Lye, 2004;Shmygol et al, 2006) which result in the release of Ca 2+ from an intracellular store through stimulation of Gq-phospholipase C (PLC)-inositol triphosphate (IP 3 ) pathway (Phillippe et al, 1997;Asokan et al, 2002;Wray et al, 2003;Zingg and Laporte, 2003;Myatt and Lye, 2004;Shmygol et al, 2006). Besides the intracellular source, there is evidence to show that the influx of extracellular Ca 2+ provides the major increase in intracellular Ca 2+ since calcium channel blockers abolished the contractions of both agonists (Perusquia and Kubli-Garfias, 1992;Kawarabayashi et al, 1997;Phillippe et al, 1997;Sultatos, 1997;Ruttner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Oxytocin and PGF 2␣ cause myometrium contractions by acting on oxytocin and prostaglandin FP receptors, respectively (Zingg and Laporte, 2003;Myatt and Lye, 2004;Shmygol et al, 2006) which result in the release of Ca 2+ from an intracellular store through stimulation of Gq-phospholipase C (PLC)-inositol triphosphate (IP 3 ) pathway (Phillippe et al, 1997;Asokan et al, 2002;Wray et al, 2003;Zingg and Laporte, 2003;Myatt and Lye, 2004;Shmygol et al, 2006). Besides the intracellular source, there is evidence to show that the influx of extracellular Ca 2+ provides the major increase in intracellular Ca 2+ since calcium channel blockers abolished the contractions of both agonists (Perusquia and Kubli-Garfias, 1992;Kawarabayashi et al, 1997;Phillippe et al, 1997;Sultatos, 1997;Ruttner et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It may therefore seem that the inhibition of the amplitude of myometrial contraction markedly observed in this study may be attributed to the prevention of MLC20 phosphorylation by DF. Activation of MLCK by CalM translocation of activated MLCK towards the contractile apparatus may be the rate-limiting step of contraction (Wray et al 2003) determining the contraction frequency of the myometrium. It would also seem that with the effect of DF being somewhat more pronounced on the amplitude than the frequency of spontaneous contractions, DF may exert less activity on MLCK activation and possibly a greater effect on prevention of MLC20 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…As Sedighi et al results indicated that R. damascena Mill decreased ileum contractions induced by KCl dose-dependently probably through stimulating the β-adrenergic receptors and inhibition of voltage-dependent calcium channels in the rat (15). The basic phasic nature of uterine contraction is critically dependent on calcium influx and on membrane potential (27)(28)(29) and R. damascena may affect calcium channels. Cyclic AMP relaxant effect on uterine smooth muscle is mediated through inhibition of calcium mobilization and the contractile apparatus (30,31).…”
Section: Discussionmentioning
confidence: 99%